IDENTIFICATION OF THE IMPACT OF EDUCATION AND MEDICATION REMINDER APPLICATION IN IMPROVING KNOWLEDGE AND ADHERENCE OF PULMONARY TUBERCULOSIS PATIENTS IN PRIMARY HEALTHCARE CENTERS IN BANDUNG - Faustincia, Ivena
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. Effective treatment and prevention methods are available. The patient’s adherence to the prescribed therapy and their understanding of TB play a crucial role in improving treatment outcomes. Several strategies have been implemented to enhance patient adherence to TB treatment, but the prevalence of TB is still high and the success rate of treatment in Indonesia remains low, leading to a continued risk of transmission in the community. This study aimed to determine the impact of education and a medication reminder application on increasing knowledge and adherence among pulmonary TB patients in two primary healthcare centers in Bandung City. The study design is a randomized experimental study with two arms, and a total of 16 participants recruited. Primary data collection included pre-test and post-test scores using the KATUB-Q questionnaire, adherence assessment through pill count and self assessment using the MARS-5 scale, and feedback from participants regarding their experience using the Jadwal Minum Obat application. The study findings indicate that the education method and medication reminder application did not significantly increase patient’s knowledge and adherence (p > 0,05). However, there was still an increase in adherence observed in the intervention group. This is evidenced by a higher percentage of drug consumption compared to the amount drug that should be taken in the intervention group (87,4 ± 4,8 %) in comparison to the control group (78,8 ± 8,3 %). Participants reported finding the medication reminder application helpful in reminding them of their medication schedule, although there were some areas for improvement identified for future iterations of the application.